Evaluating Teachers’ Performance: A Need for Effective Teaching - Siti Aimah; Bambang Purwanto (Soegijapranata Catholic University, 2019)
This article reports a study, which aims to evaluate the EFL teachers’ performance of teaching in the English Education Department of Universitas Muhammadiyah Semarang (Unimus). The study was conducted to find out how competent the English lecturers/university teachers in the Department are in conducting an English Language Teaching (ELT) program in the classroom. A case study was employed to five teachers who taught the fifth-semester students in the Academic Year of 2017/2018. Through an observation during their teaching and learning process by involving four observers and through a questionnaire distributed to the 13 students in the fifth semester. The study shows the different results of teachers’ performance from both the teachers’ and students’ perspectives. Based on observation, it is revealed that the teachers’ performance in ELT program does not show a satisfactory result yet. The teachers tend to use unvarying methods and focus on certain students without knowing that some of them have learning problems. Meanwhile, from the questionnaire distributed to the students, it shows that the teachers have good competencies in conducting an ELT program in the classroom in which one of the indicators is seen from the personality of the teachers.